Development of Fire Retardant formulations for Plywood Protection - Poonia, Pawan Kumar; Tripathi, Sadhna; Kaur, Inderjeet (Indian Forester, 2015)
Wood is one of the most sustainable, aesthetically pleasing and environmentally benign materials. Dry wood materials are susceptible to fire hazards and results heavy losses of life and materials every year; hence protection against fire is necessary. The present study deals with the treatment of plywood with two different fire retardant cum preservative compositions by vacuum pressure method to offer protection against fire and bio-deterioration. The performance of treated plywood against fire is tested by flame penetration test, inflammability test and rate of burning test as per Indian Standards. The results showed that the mean time taken by control i.e. 17:24 and 19:44 minutes was significantly different (P < 0.05) from both compositions "A" (32:07 and 30:32 minutes) and "B" (42:03 and 33:53 minutes) in Flame penetration test and Inflammability test respectively whereas, in rate of burning test the time of weight loss from 30 to 70 percent were 1:44 minutes in control which was significantly lower than both the composition "A" (26:22 minutes) and "B" (27:58 minutes). Hence, it may be concluded that both the formulations performed as per standard and it can be recommended for application.